Does the Source of FDI Matter? Analysing China/BRICS and Western Investment in Zambia's Mining Sector - Oscar Kaonga; Lubinda Haabazoka (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines divergent patterns of China/BRICS and Western foreign direct investment (FDI) in Zambia's mining sector, investigating whether investor national origin shapes investment motivations, governance behaviour, and sectoral outcomes amid intensifying global competition for critical minerals. Design/methodology/approach – A sequential explanatory mixed-methods design is employed, combining panel econometric modelling of bilateral FDI inflow data (2000–2023) using Fixed Effects and Poisson Pseudo-Maximum Likelihood (PPML) estimators, with 32 semi-structured key informant interviews analysed through thematic analysis in NVIVO 14. Finding/Results – Western FDI shows a significantly larger estimated sensitivity to mineral royalty rates and political stability, while China/BRICS FDI shows a significantly larger estimated association with bilateral diplomatic intensity. Qualitative evidence reveals that China/BRICS operations exhibit lower local content compliance ( 44% vs 68%) and weaker labour standards, whereas Western ESG frameworks do not uniformly translate into superior on-the-ground outcomes. A novel 'Bundled Location Premium' mechanism, whereby Chinese investors couple mining equity with concessional infrastructure finance, creates a competitive asymmetry not captured by standard FDI theory. Originality/Value – This study uses a systematic mixed-methods comparing China/BRICS and Western FDI determinants in a single African mining jurisdiction over a twenty-three-year panel. It extends the OLI paradigm for geopolitically differentiated FDI behaviour, introduces the 'Bundled Location Premium' construct, and advances five evidence-based policy recommendations for resource-dependent states.